Effect of motorcycle exhaust pipe temperature and electrical circuit on harvested dc power from thermoelectric generators - Mirmanto, M.; Tira, H.S.; Pabriansyah, A. (Universitas Mataram, 2020)
The need for energy consumption nowadays becomes very important things, especially the need for electrical energy. Technology to convert heat into electricity directly can be realized using thermoelectric generators. To know the thermoelectric generator performance, this study performs an investigation of thermoelectric generator operated using motorcycle exhaust heat to generate DC power. Three identical thermoelectric generators model TE-MOD-5W5V-35S were used in this investigation. To generate different high temperatures the motorcycle was run at 1600 rpm, 2100 rpm, 3100 rpm. The circuits examined were series, parallel and combination of the two. All data were recorded using DAQ MX 9714 NI data logger that was connected to the PC using LabView program. The loads used in the current measurements were a thermoelectric cooler module model SP1848 and a fan 12 V - 0.13 A. Those two loads were installed in a parallel circuit. The results show that the tests without load produce the highest voltage, while the tests with the load result in the highest power. Increasing the temperature difference increases the power, and the parallel circuit results in the biggest power but the lowest voltage. The highest voltage of 3.3 V with series circuit was attained, and the highest power of 0.133 W with a parallel circuit was also obtained.